The Effectiveness of Community of Inquiry Learning and Learning Styles Towards Students’ Concept Mastery - Syarifuddin Syarifuddin; Dewi Sartika (JECED : Journal of Early Childhood Education and Development, 2022)
This study was conducted to identify whether there was a positive effect of the Community of Inquiry learning and learning styles on students’ concept mastery. The samples involved were 113 students, consisting of 56 students for the experimental group and 57 students for the control class. This research was a quasi-experimental design. The results of this study concluded that there was a significant difference in the concept mastery of the students who used the Community of Inquiry learning compared to the group of students who used cooperative learning. Besides, there were significant differences in concept mastery of students taught using the community of inquiry learning compared to those taught using cooperative learning in terms of student learning style visual, auditory, and kinesthetic. There was no infection of the use of community of inquiry learning with cooperative learning and learning styles on students’ concept mastery.